Ownership Concentration and Agency Cost on the Performance of Johannesburg Stock Exchange Listed Companies - Mosimanyane, Lethabo; Marozva, Godfrey (Acta Universitatis Danubius. Œconomica, 2023)
This article examines the relationship between ownership concentration as a proxy to alleviating agency costs on the performance of the JSE-TOP40 listed companies from 2010-2018. The two-step generalised method of moments methodology was employed to examine the nexus. The results revealed that foreign ownership does not influence company performance. Whereas performance was found to deteriorate with increase in managerial ownership. In many instances, companies are encouraged to align the managerial ownership with company performance by choosing to shorten or prolong their vesting period. Therefore, future studies might need to empirically study the same relationship accounting for management share option schemes.